Analisa Dampak Pencemaran Lingkungan Tiongkok Terhadap Aspek Human Security di Jepang - Yulia Widiyani; Marten Hanura (Journal of International Relations Diponegoro, 2020)
Environmental issue has been developing in the international community the past years, not exceptionally for China. China has a serious environmental problem such as land, air and water pollution. Unfortunately, China’s environmental problems do not only af ecting the country itself but also posing threat to its neighboring country like Japan. Specifically, this study analyzes how environmental pollution in China can take into account of human security in Japan. To analyze this phenomenon, this research will use the concept of human security. The concept gives a novel insight into environmental issue. This study uses qualitative research methods with the type of descriptive research. The results of this study explain about environmental pollution that occurs in China is directly and indirectly causing environmental damage in Japan and poses a threat to the human security dimension for Japanese society.